Síntese de óxidos de ferro nanoestruturados dispersos em materiais carbonosos e porosos, estudo do seu comportamento térmico e aplicações em processos de adsorção - Gonçalves, Gustavo dos Reis (2015)
Nanostructured materials exhibit many interesting physical and chemical properties, among which we can mention the magnetic properties, due to their great relevance for technological applications. This work aims at the synthesis of nanoparticles of iron oxides or other iron compounds supported on porous carbon materials derived from the endocarp of babassu coconut, with special emphasis on the physical and chemical transformations caused by heat treatments and on their potential for use in liquid phase adsorption. Two different carbon supports were used: a char obtained by the carbonization of the endocarp of babassu coconut and an activated carbon prepared from the same precursor by chemical activation with H3PO4. The synthesis of the nanocomposites was conducted by aqueous impregnation, using Fe(NO3)3?9H2O and NH4OH as the source of iron and the precipitating agent, respectively. The techniques used for the characterization were: elemental analysis, thermogravimetry, differential thermal analysis, X-ray diffraction, Mössbauer spectroscopy, textural analysis by nitrogen adsorption and measurements of magnetic properties. The nanoparticles were identified as iron oxides homogeneously dispersed in the porous carbon support, with average size in the order of nanometers and showing superparamagnetic behavior at room temperature. The execution of heat treatments in a nitrogen atmosphere at predetermined temperatures of 700, 800, 900 and 1000° C led to crystallite growth and to the formation of new phases due to the chemical reduction of the iron oxide nanoparticles dispersed in the carbon-rich support. Depending on the heat treatment temperature and on the type of carbon support, the dominant phases were: iron oxides (Fe2O3, Fe3O4), metallic iron (a-Fe and ?-Fe(C)), iron carbide (Fe3C), iron phosphate (FePO4 and Fe2P2O7) and iron phosphide (Fe2P). The results of this study showed that the method employed enables the synthesis of nanocomposites with diverse chemical and structural characteristics, depending on the conditions of preparation and on the subsequent execution of heat treatments.